2009
DOI: 10.1128/jvi.02381-08
|View full text |Cite
|
Sign up to set email alerts
|

Noncytolytic Clearance of Sindbis Virus Infection from Neurons by Gamma Interferon Is Dependent on Jak/Stat Signaling

Abstract: The alphavirus Sindbis virus (SINV) causes encephalomyelitis in mice byAlphaviruses in the family Togaviridae are enveloped, plusstrand, mosquito-borne RNA viruses that can cause encephalomyelitis. Sindbis virus (SINV), the prototype alphavirus, causes arthritis and rash in humans (39, 48) and encephalomyelitis in mice, a small-animal model for study of the pathogenesis of acute encephalitis (32). Age is an important determinant of outcome, and neonatal mice die within the first few days after infection, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 86 publications
(110 reference statements)
3
66
0
Order By: Relevance
“…6B). This confirmed results of previous studies showing a lack of STAT1 phosphorylation during SINV infection of AP-7 or CSM14.1 neurons (62).…”
Section: Alphavirus Multiplication Is Restricted In Differentiated Nesupporting
confidence: 82%
See 1 more Smart Citation
“…6B). This confirmed results of previous studies showing a lack of STAT1 phosphorylation during SINV infection of AP-7 or CSM14.1 neurons (62).…”
Section: Alphavirus Multiplication Is Restricted In Differentiated Nesupporting
confidence: 82%
“…The protective role of IFNs against encephalitic virus infections has been demonstrated in other in vitro systems and in vivo. Pretreatments of a variety of cultured cells, including neurons, with IFN-␣, -␤, or -␥ prevents more than 99% of infectious SINV production, significantly reduces synthesis of viral proteins, and preserves cellular viability and protein synthesis (20,62,70). The G3A mutation in VEEV TC-83 renders this strain responsive to IFN-␣/␤ priming and is correlated with decreased mortality in weanling mice (25,26,70).…”
Section: Figmentioning
confidence: 99%
“…Production of IFN from IP cells allows these cells to transition into an 'activated population' (AP) where viral defenses slow virus release and further enhance IFN production. Over time, this population will gradually become a 'protected population' (PP) of cells that have cleared the infection and maintain active antiviral defense programmes [22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
“…Similar studies have been done using SINV infection in immunodeficient SCID or RAG-1 deficient mice. The studies found the clinical outcomes of SINV infection in immunodeficient neonatal mice to be comparable to that in immunocompetent neonatal mice (Burdeinick-Kerr et al, 2009;Levine & Griffin, 1993). Results of these studies suggest that the adaptive immune response does not play a role in the development of RRV-induced myositis and is not essential in the clinical outcome of alphaviral disease.…”
Section: Cellular Factors In Alphavirus Induced Myopathiesmentioning
confidence: 99%